Projections of future soil temperature in the western part of the Southeastern Anatolia Project region, Türkiye - Tekkanat, İlyas Sadık (Acta geographica Slovenica, 2025)
Soil temperature (Ts) is crucial for land use and soil management. It has gained importance in climate change research as it reflects the interactions between the atmosphere and biosphere. This study evaluates Ts changes at depths of 5, 10, 20, 50, and 100 cm in the western part of the Southeastern Anatolia Project (W-SAP) region of Türkiye, which has a Mediterranean and hot semi-arid climate, for the period 2030–2090 compared to 1981–2010. The Soil Temperature and Moisture Model (STM2) is used to generate Ts estimates. A temperature increase of 0.7–3.0 °C (RCP4.5) and 0.9–5.5 °C (RCP8.5) is predicted for the 21st century. Extreme Ts values in late-century summers may hinder crop planning. The research provides the first future Ts projections in W-SAP and offers important agro-climatic insights.